A wedding wager - Feather, Jane (Pocket Books, 2011)
Lady Serena Grantley was born to the nobility, but fortune's whim placed her in control of her gamester stepfather, who uses her beauty to lure young men to his gambling tables. Serena even dismissed her first love, the Honorable Sebastian Sullivan, at her stepfather's command. But when he attempts to force her into a liaison with a dissolute earl, Serena resolves to do his bidding no more. Sebastian is the only man who ever captured her heart, and it is to him she turns. . . . Torn between family loyalty and the woman he loves, Sebastian faces a devilish dilemma. His uncle is ailing, and time is running short. Desperate to find a solution, Sebastian conceives a dangerous plan--a wager that could bring him and Serena happiness at last . . . or separate them forever.